2015
DOI: 10.1186/s12888-015-0560-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of insight with medication adherence and the impact on outcomes in patients with schizophrenia and bipolar disorder: results from a 1-year European outpatient observational study

Abstract: BackgroundMany patients with schizophrenia and bipolar disorder have impaired insight and low medication adherence. The aim of this post hoc analysis was to explore the relationship between insight and medication adherence.MethodsWe included 903 patients with schizophrenia or bipolar disorder who participated in an observational study conducted in Europe on the outcomes of patients treated with two oral formulations of olanzapine over a 1-year period. Evaluations included Clinical Global Impression (CGI), Glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
58
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 27 publications
6
58
2
2
Order By: Relevance
“…Measures of several dimensions of insight were shown to correlate with measures of attitude toward medication46 or therapeutic alliance;19 additionally, both insight and therapeutic alliance seem to predict the attitude toward medication,60 which indicates that these 3 variables are closely related. More detailed analyses that examined the relationship among these variables suggested that the effect of insight and therapeutic alliance on adherence is indirect and likely mediated by attitude toward medication 22,27,46.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Measures of several dimensions of insight were shown to correlate with measures of attitude toward medication46 or therapeutic alliance;19 additionally, both insight and therapeutic alliance seem to predict the attitude toward medication,60 which indicates that these 3 variables are closely related. More detailed analyses that examined the relationship among these variables suggested that the effect of insight and therapeutic alliance on adherence is indirect and likely mediated by attitude toward medication 22,27,46.…”
Section: Discussionmentioning
confidence: 91%
“…A brief summary of results from each of the studies is provided in Tables 1 and 212,1934 (prospective and post hoc analyses) and Tables 3 and 43553 (cross-sectional). Most of the studies were conducted in patients with schizophrenia or schizophrenia-like disorders (75%, 27/36).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It also would be useful to understand if the relationships observed among variables in the current sample are specific to bipolar disorder or are typical of various forms of psychopathology by including other psychiatric and non-psychiatric comparison groups. Furthermore, patients with mania can sometimes exhibit lower insight into their illness (Novick et al, 2015), and therefore the self-report nature of several of the measures should be considered, especially given the lack of associations identified with manic severity. In addition, there was low ethnic-minority representation in our sample and thus the utility of the VLQ in more diverse samples should continue to be examined.…”
Section: Discussionmentioning
confidence: 99%